Estudo do efeito neuroprotetor da berberina e emulsão de berberina sobre comportamento tipo-autista: estudo pré-clínico - Medeiros, Fabiana Durante de (2019)
Introduction: Behavioral changes such as social interaction deficits, restrictive and repetitive patterns of behavior; changes in learning and memory occur in response to maternal immune activation (MIA), characterized as behavior of individuals with Autistic Spectrum Disorder (ASD). New therapeutic alternatives have been suggested to improve the symptoms of this disorder, among them, berberine (BBR) has presented positive results in the treatment of neurological and psychiatric diseases. Objective: The objective of this study was to evaluate the neuroprotective effect of BBR on behavioral, biochemical and blood-brain barrier (BBB) responses of rats exposed to LPS in the prenatal period. Methods: Pregnant female Wistar rats received intraperitoneal (ip) injection of LPS by submitting male offspring to the animal model of autism (experimental group) and the saline group received ip injection of saline solution. Females started treatment with BBR 1 h after LPS application, 9.5 gestational day until PND21, day of weaning. Behavioral and memory tests were carried out in PND 45 and PND 60; evaluation of BBB in PND 22 and PND 60, biochemical analysis in PND 60, hippocampal structure; analysis of milk in PND 10 and the plasma concentration of dams and offspring in the PND 10. Results: MIA caused by the administration of LPS caused in adult offspring behavioral changes consistent with ASD, as a reduction in reciprocal social behavior; reduction in aversive memory. BBR presented a reversal of autistic-type behavior and exerted neuroprotective effect, increased reciprocal social behavior; increased aversive memory. Conclusion: Preventive administration of BBR (100 mg / kg) in the matrix 1 hour after MAI provided effects in preventing autistic type behavior in offspring. The BBR presented a behavior reversal and had a neuroprotective effect, specifically, an increase in reciprocal social behavior and increase in aversive memory.